2017
DOI: 10.1186/s12863-017-0470-1
|View full text |Cite
|
Sign up to set email alerts
|

Fat mass and obesity associated (FTO) gene influences skeletal muscle phenotypes in non-resistance trained males and elite rugby playing position

Abstract: Background FTO gene variants have been associated with obesity phenotypes in sedentary and obese populations, but rarely with skeletal muscle and elite athlete phenotypes.MethodsIn 1089 participants, comprising 530 elite rugby athletes and 559 non-athletes, DNA was collected and genotyped for the FTO rs9939609 variant using real-time PCR. In a subgroup of non-resistance trained individuals (NT; n = 120), we also assessed structural and functional skeletal muscle phenotypes using dual energy x-ray absorptiometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 52 publications
5
33
0
Order By: Relevance
“…There was an association between FTO rs9939609 AA and lean body mass; however, that association disappeared when controlling for fat mass 41,47 . Recent studies have reported over-representation of FTO rs9939609 AA genotypes in heavier athletes 48,49 , however, none has investigated how the body mass and muscle mass are affected by this genotype in those athletic populations. We previously demonstrated that the T-allele is associated with higher appendicular and arm lean mass in untrained young men 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an association between FTO rs9939609 AA and lean body mass; however, that association disappeared when controlling for fat mass 41,47 . Recent studies have reported over-representation of FTO rs9939609 AA genotypes in heavier athletes 48,49 , however, none has investigated how the body mass and muscle mass are affected by this genotype in those athletic populations. We previously demonstrated that the T-allele is associated with higher appendicular and arm lean mass in untrained young men 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported over-representation of FTO rs9939609 AA genotypes in heavier athletes 48,49 , however, none has investigated how the body mass and muscle mass are affected by this genotype in those athletic populations. We previously demonstrated that the T-allele is associated with higher appendicular and arm lean mass in untrained young men 49 . It therefore appears that FTO AA-genotype individuals have lower skeletal muscle mass and are at higher risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Loos et al have shown that homozygous Fto −/− mice have postnatal growth retardation, obviously decreasing in adipose tissue, and LBM 40 . According to the studies of athletes the T-allele of FTO gene rs9939609 is associated with increased lean mass for the elite rugby athletes, and for combat sports athletes the A-allele is related with decreased slow-twitch muscle fibers 29,42 . AMPK (AMP-activated protein kinase) is an essential part of skeletal muscle lipid metabolism and is the major cellular energy sensor.…”
Section: Discussionmentioning
confidence: 99%
“…But the exact biological functions of this gene are unknown yet. In recent researches, FTO gene is proved the association with lean mass 22,23,[26][27][28][29][30][31] . Zillikens et al reported a series of SNPs of FTO associated with LBM and appendicular lean mass (ALM) 30 .…”
mentioning
confidence: 99%
“…As part of the ongoing RugbyGene project [ 12 , 13 , 34 ], a total of 1105 individuals were recruited and gave written informed consent to participate in the present study. An a priori calculation for 80% power to detect a small effect size (w) of 0.1 required a sample of >785 participants.…”
Section: Methodsmentioning
confidence: 99%